1996
DOI: 10.1073/pnas.93.21.11848
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species are downstream mediators of p53-dependent apoptosis.

Abstract: Reactive oxygen species (ROS) have been implicated as potential modulators of apoptosis. Conversely, experiments under hypoxic conditions have suggested that apoptosis could occur in the absence of ROS. We sought to determine whether a central modulator of apoptosis, p53, regulates the levels of intracellular ROS and whether a rise in ROS levels is required for the induction of p53-dependent apoptosis. We transiently overexpressed wild-type p53, using adenoviral gene transfer, and identified cell types that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
303
2
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 542 publications
(329 citation statements)
references
References 27 publications
(24 reference statements)
19
303
2
5
Order By: Relevance
“…This increase in the level of lipid peroxidation causes the loss of mitochondrial membrane potential, observed after treatment with CPT for 2.5 h. These results are consistent with those of other investigators, who concluded that lipid peroxidation and oxidative stress together may impair a variety of intra-and extramitochondrial membrane transport systems that may contribute to apoptosis. 28,38 In mammalian cells, an increase in cellular ROS production has been observed in an apoptotic process triggered by various stimuli, 33,39,40 and has been claimed to be responsible for the depolarization of Dc m and subsequent cell death. 33,39,41 Furthermore, some authors suggest that ROS generation precedes caspase activation, 33,38 whereas others claim that it is a consequence.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in the level of lipid peroxidation causes the loss of mitochondrial membrane potential, observed after treatment with CPT for 2.5 h. These results are consistent with those of other investigators, who concluded that lipid peroxidation and oxidative stress together may impair a variety of intra-and extramitochondrial membrane transport systems that may contribute to apoptosis. 28,38 In mammalian cells, an increase in cellular ROS production has been observed in an apoptotic process triggered by various stimuli, 33,39,40 and has been claimed to be responsible for the depolarization of Dc m and subsequent cell death. 33,39,41 Furthermore, some authors suggest that ROS generation precedes caspase activation, 33,38 whereas others claim that it is a consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a Ref1-thioredoxin complex may also participate in the regulation of p53 by ROS. The role of ROS in p53-mediated apoptosis has been demonstrated (Johnson et al, 1996). Furthermore, an increased tumor cells capacity for undergoing apoptosis in response to ROS was also shown to be p53-dependent (Graeber et al, 1996).…”
Section: Thioredoxin E Ects On Transcription Factorsmentioning
confidence: 92%
“…33 In addition, p53 might be responsible for the generation of ROS. 34 Furthermore, several direct lines of evidence imply that the pro-apoptotic activity of p53 might be independent of its function as a transcription factor. 35,36 The pathways whereby p53 leads to execution of apoptotic program seem to be multiple and may strongly depend on the cell type and the nature of apoptotic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the role of ROS and Bax as well as mitochondrial cytochrome c release as downstream mediators in the anti-cancer drug-induced apoptosis and in the models of apoptosis induced by transient p53-overexpression have been recently controversially discussed. 3,34,[37][38][39] In the model of ROS-driven apoptosis, the generation of ROS has been suggested as a primary regulatory component followed by the activation of caspases and caspase-dependent loss of MMP. 34,38 Consequently, this form of cell death could be prevented by antioxidants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation